Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Tanzania - Mwinuka, Lutengano (International Food Policy Research Institute, 2014)
The overall purpose of this study is to develop a country‐specific capacity‐strengthening strategy to meet the strategic analysis and knowledge management objectives of the country CAADP process. The specific objective is to identify areas for improving the quality and utility of agricultural policy analysis and investment planning and implementation, M&E, and knowledge management at the country level. The study’s findings will be useful in designing and establishing the country SAKSS. Targeted respondents for the study included government ministries and agencies, local organizations involved in agricultural and food policy research, local and international nongovernmental organizations (NGOs), and institutions of learning and research.